Advanced Computing Solutions for Healthcare - Rajagopal, Sivakumar; P., Prakasam; E., Konguvel; Subramaniam, Shamala; Safaa Sadiq Al Shakarchi, Ali; Prabadevi, B. (Bentham Science Publishers, 2025)
<div style=